Empathy, Sympathy and Witnessing Suffering in Damon Galgut's Small Circle of Beings and The Guardian - Pawlicki, Marek (Journal of southern African studies, 2025)
This article offers a close reading of Damon Galgut's Small Circle of Beings and The Guardian from the perspective of affect studies, specifically the theories that concentrate on emotions experienced as a result of empathy and sympathy. I argue that in both novellas, Galgut explores the power and the limits of empathy and sympathy by describing moments of emotional closeness and distance between his protagonists. Galgut's novellas not only examine empathy but also elicit a readerly response that involves both empathic involvement and reflective detachment. This combination of involvement and detachment makes it possible for readers to appreciate the intricate emotional dynamic of relationships between protagonists. While emotional involvement, achieved through empathy, enables readers to understand the viewpoint of Galgut's narrators, detachment makes them capable of transcending their perspectives to better understand those whose physical and mental suffering is described indirectly. This combination of empathic involvement and reflective detachment is necessary to appreciate the complexities of the protagonists' interactions, in which empathy is tested to its limits.